Orchids’ micropropagation for to the sustainable management of native species from Parque Nacional y Área Natural de Manejo Integrado Cotapata (PN-ANMI Cotapata), La Paz-Bolivia - López Roberts, Cristina (Universidad de Costa Rica, 2015)
Bolivia is one of eleven countries with the highest biodiversity in earth, due to its variety of ecological belts, ecotones, biogeographic affinities, heterogenic habitats and total species number (Ibish 1996). Concerning to flora, approximately 20,000 angiosperms species have been registered (Beck 1998) and 1,500 of them are included in the Orchidaceae family. The region with the highest orchid diversity corresponds to the Yungas Mountain Forest which covers 4% of the national extension and has 60% of the species, being 80% of them endemic of the zone (Vásquez, 2004).